2024
DOI: 10.1021/acs.inorgchem.3c04105
|View full text |Cite
|
Sign up to set email alerts
|

Halobenzene Adducts of a Dysprosocenium Single-Molecule Magnet

Sophie C. Corner,
Gemma K. Gransbury,
Iñigo J. Vitorica-Yrezabal
et al.

Abstract: Dysprosium complexes with strong axial crystal fields are promising candidates for single-molecule magnets (SMMs), which could be used for high-density data storage. Isolated dysprosocenium cations, [Dy(Cp R ) 2 ] + (Cp R = substituted cyclopentadienyl), have recently shown magnetic hysteresis (a memory effect) above the temperature of liquid nitrogen. Synthetic efforts have focused on reducing strong transverse ligand fields in these systems as they are known to enhance magnetic relaxation by spin-phonon mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…For 3-Dy , there are four ion pairs within the P unit cell; thus, the atomic coordinates of the two least disordered ion pairs were used for comparative purposes and for subsequent calculations. Increasing the size of the halogen in the coordinated solvent leads to increased mean Dy–X distances [ 2-Dy : 2.358(12) Å; 4-Dy : 2.920(3) Å; 5-Dy : 3.064(3) Å] as expected; subtracting the covalent radii of the halogens (F: 0.64 Å; Cl: 0.99 Å; Br: 1.14 Å) from these distances gives a value of ca . 1.93 Å for both X = Cl and Br.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…For 3-Dy , there are four ion pairs within the P unit cell; thus, the atomic coordinates of the two least disordered ion pairs were used for comparative purposes and for subsequent calculations. Increasing the size of the halogen in the coordinated solvent leads to increased mean Dy–X distances [ 2-Dy : 2.358(12) Å; 4-Dy : 2.920(3) Å; 5-Dy : 3.064(3) Å] as expected; subtracting the covalent radii of the halogens (F: 0.64 Å; Cl: 0.99 Å; Br: 1.14 Å) from these distances gives a value of ca . 1.93 Å for both X = Cl and Br.…”
Section: Resultsmentioning
confidence: 63%
“…During various attempts to isolate 2-Dy , 3-Dy , 4-Dy , and 5-Dy , the unintentional introduction of trace amounts of coordinating solvents led to the formation of oxygen-bound adducts that could be identified by SCXRD, including [Dy­(Cp*) 2 (DME)]­[Al­{OC­(CF 3 ) 3 } 4 ] ( 10-Dy ) and [Dy­(Cp*) 2 (PhBr-κ- Br )­(THF)]­[Al­{OC­(CF 3 ) 3 } 4 ] ( 11-Dy ). A small portion of “[{Dy­(Cp*) 2 }­{Al­[OC­(CF 3 ) 3 ] 4 }]” dissolved in THF, layered with n -hexane, and stored at −30 °C gave several crystals of [Dy­(Cp*) 2 (THF) 2 ]­[Al­{OC­(CF 3 ) 3 } 4 ] ( 12-Dy ); the two bound THF molecules are akin to the closely related analog [Dy­(Cp ttt )­(Cp*)­(THF) 2 ]­[Al­{OC­(CF 3 ) 3 } 4 ] and the comparable group 3 complex [Sc­(Cp*) 2 (THF) 2 ]­[BPh 4 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the incomplete photocyclization in the solid state as well as the remote character of these changes with respect to the ligand eld of the Dy III centers. This suggests that the dte-type ligands should be attached to a high-performance SMM such as dysprosocenium- [53][54][55] or lanthanide-bisamide-type 56 complexes to achieve substantial light-switchable magnetic properties. Most importantly, in the linear molecule of 1 it was possible to distinguish two processes of slow relaxation of the magnetization associated with the central and peripheral dysprosium ions.…”
Section: Discussionmentioning
confidence: 99%
“…In their contribution, Chilton, Mills, and colleagues demonstrated that the sought-after SMM candidate [Dy­(Cp*) 2 ] + (Cp* = {C 5 Me 5 }) cannot be isolated free of equatorial donor coordination, even when extremely weakly donating haloarenes are used, resulting in the first f-block bis-haloarene adducts [Dy­(Cp*) 2 (PhX-κ-X) 2 ]­[Al­{OC­(CF 3 ) 3 } 4 ] (X = F, Cl, Br) . Even when the size of the supporting ligands is increased, as in a second paper by Chilton and Mills that features [Dy­(Cp*)­(Cp ttt )­(X n C 6 H 6– n )] + (Cp ttt = {C 5 H 2 -1,2,4- t Bu 3 }), equatorial haloarene adducts could be isolated, although this class has better SMM characteristics than the previous due to the reduced equatorial donation . Roesky and co-workers have explored the influence of arsolyl ligands, {η 5 -AsC 4 R 4 }, on the coordination environment and magnetic properties of several Ln III ions (Sm, Dy, and Er), finding that the nuclearity of [RE­(η 8 -COT)­(η 5 :μ n -AsC 4 R 4 )] n (Ln = Sm, Dy, Er; n = 1, 2; COT = {C 8 H 8 }) complexes depends on the steric protection at the 2,5 positions of the {AsC 4 R 4 } ring with large Sm III ions, but with small Dy III and Er III ions, monomeric complexes are obtained even with small R groups such as in {AsC 4 Me 4 }.…”
mentioning
confidence: 99%